Diversity of anaerobic gut fungi - Ho, Yin Wan; Abdullah, Norhani; Syed Salim, Syed Jalaludin; Kudo, H. (1990)
The anaerobic gut fungi, studied so far showed two types of growth patterns - monocentric and polycentric. For a long timfi. the fungi isolated and cultured were all monocentric types. It was only recently that Akin and Rigsby (1987) reported tte presence of polycentric anaerobic fungi in the rumen of cattle. Since then, polycentric fungi have been observed by other workers in the rumen of cattle and buffalo (Phillips, 1988, Ho et al., 1988a: 1990).